Respuesta :

Answer:

[tex]x = 3[/tex]

Step-by-step explanation:

2x+y=4

Y=x-5

[tex]2x+(x - 5)=4 \\ 2x + x - 5 = 4 \\ 3x = 5 + 4 \\ 3x = 9 \\ \\ x = \frac{9}{3}

\\ x = 3[/tex]

Answer:

x = 3

y = -2

Step-by-step explanation:

2x + y = 4; y = x - 5

First name the equation

2x + y = 4 ...(1)

y = x - 5. ...(2)

Now Substitute the value of y in equation (1)

2x + y = 4

2x + (x - 5) = 4

2x + x - 5 = 4

3x = 4 + 5

3x = 9

x = 9 ÷ 3

x = 3

Now, put the value of x = 3 in equation (2)

y = x - 5

y = 3 - 5

y = - 2

Thus, The Value of x is 3 and the value of y is -2

FOR VERIFICATION ONLY:

2x + y = 4

2(3) + (- 2) = 4

6 - 2 = 4

4 = 4

y = x - 5

- 2 = 3 - 5

- 2 = - 2

Hence, L.H.S = R.H.S

-TheUnknownScientist